The effects of plyometric training on knee joint angle-torque relationship in elite handball players - Sanli, G.; Uzun, S.; Tatar, Y.; Cakir, Z.; Gercek, N.; Ramazanoglu, N. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to examine the effects of 8 weeks plyometric training program on knee joint angle-toque relationship in elite handball players. A total of 7 male handball players (Age: 22.0±4.5 years; Weight: 95.7±12.7; Height: 187.4±4.4 cm) participated in the study. Concentric isokinetic peak torque, angle of peak torque and average power was assessed for the knee extensors and flexors at 180°/s before and after training program. No significant difference was found at the angle of peak toque values between pre- and post-test (p > 0.05). However difference was detected in peak torque and average power values of knee extensors (p < 0.05). It is concluded that plyometric training is not an effective training modality to alter knee joint angle-toque relationship in elite handball players.